2000
DOI: 10.1021/cm990485u
|View full text |Cite
|
Sign up to set email alerts
|

Lewis Acid Doped Polyaniline. Part II:  Spectroscopic Studies of Emeraldine Base and Emeraldine Hydrochloride Complexation with FeCl3

Abstract: It is demonstrated that Lewis acid doping of polyaniline in the oxidation state of emeraldine can be conveniently monitored by 57 Fe Mo ¨ssbauer spectroscopy if FeCl 3 is used as the dopant. The spectrum of doped polyaniline consists of two doublets with distinctly different Mo ¨ssbauer parameters which can be unequivocally ascribed to two types of complexing sites (amine and imine nitrogens). From the temperature dependence of the isomer shift and the recoil free absorption, we have calculated Mo ¨ssbauer la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
53
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(58 citation statements)
references
References 17 publications
4
53
0
Order By: Relevance
“…The ratio of the absorbance at 1982 nm to that at 1460 nm is much great for water than the ratio of 1902 nm to 1460 for acetonitrile, which suggests that the equilibrium is shifted more toward zwitterion formation in water than in acetonitrile. The near-IR bands (except for the band in water at 1982 nm) are not very broad -in sharp contrast to the situation in doped polyanilines [39]. The broadness of the relevant near-IR peaks in polyaniline has been attributed to changes in the conformations of the polymer, which conformations are not so important in the smaller sized oligomers.…”
Section: Tablementioning
confidence: 78%
“…The ratio of the absorbance at 1982 nm to that at 1460 nm is much great for water than the ratio of 1902 nm to 1460 for acetonitrile, which suggests that the equilibrium is shifted more toward zwitterion formation in water than in acetonitrile. The near-IR bands (except for the band in water at 1982 nm) are not very broad -in sharp contrast to the situation in doped polyanilines [39]. The broadness of the relevant near-IR peaks in polyaniline has been attributed to changes in the conformations of the polymer, which conformations are not so important in the smaller sized oligomers.…”
Section: Tablementioning
confidence: 78%
“…This electrochemical response is stable. The accepted mechanism for polaron formation PANI is that the lone pair on the imine nitro- The literature data on PANI doping with Lewis acids are scarce [44,45]. It has been reported that Lewis acid doping of PANI with FeCl 3 gave significant changes of UV-vis-NIR spectra showing a broad absorption that can be treated as a spectroscopic manifestation of charge carrier delocalization.…”
Section: Resultsmentioning
confidence: 99%
“…In most cases, these applications are based on registration of changes in optical, electrical, chemical and electrochemical characteristics of PANI [3][4][5][6], which are determined by its doping and oxidation degrees. Along with the acidbase interactions, PANI can reversibly interact with cations of Li + and transition metals through mechanisms of pseudo-doping or Lewis acid doping [7][8][9][10][11]. These interactions lead to changes in electronic characteristics, internal hydrogen bonding and conformation of emeraldine base (EB); that causes a bathochromic (red) shift of the exciton band in optical spectra of the solutions and/or an appearance of polaron absorption features [6,[12][13][14].…”
Section: Introductionmentioning
confidence: 99%